Robust Yaw Stability Control of Commercial Vehicles - Jae-Hoon Jeong; Baek-Soon Kwon (IEEE Access)
This paper describes a robust yaw stability control for commercial vehicles. In the case of commercial vehicles, parameter variations are relatively large compared to passenger vehicles due to significant variations in load conditions. The parameter variations in commercial vehicles can cause performance deterioration of a yaw stability controller designed with nominal parameters. So, it is necessary to design a robust yaw stability controller to guarantee its performance against parameter variations. In this study, the range of changes in significant parameters affecting the cornering behavior of the vehicle was analyzed, and a stochastic distribution was assumed for the changes. The methods of stochastic root locus and parameter sensitivity reduction are adopted to design a robust yaw stability controller. Computer simulations have been conducted to evaluate the stability and robust performance of the proposed controller. The simulations show that the proposed robust yaw stability controller is effective against parameter variations in commercial vehicles.